Integrasi Nilai-Nilai Pendidikan Islam Dan Kearifan Lokal Dalam Pengembangan Kurikulum Pendidikan Berbasis Karakter - Muhammad Irham Zamzami; Hoerussifa; Yuan Riva Azahra; Nurul Mubin (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
This article provides an in-depth analysis of the integration of Islamic educational values and local wisdom in the development of character-based education curricula in Indonesia. In the context of national education facing the challenges of globalization and dynamic socio-cultural changes, developing a curriculum that can shape students’ character to be faithful, noble in character, and deeply rooted in local culture is highly important and relevant. This study employs a qualitative method with a literature review approach, involving critical analysis of various primary and secondary sources, including the Qur’an, hadith, academic books, and scientific journals published in the last five years. The discussion focuses on three main aspects: first, the concept of Islamic educational values as a moral and spiritual foundation; second, the values of local wisdom that contain norms, ethics, and cultural practices of the community; and third, strategies for effectively integrating these two value systems into a character-based curriculum. The findings show that integrating Islamic educational values and local wisdom not only enriches the learning materials but also increases the relevance of education to the students’ socio-cultural context and strengthens the formation of holistic and balanced character. However, the implementation of this integration still faces challenges, such as limited teacher competence, a lack of locally-based learning resources, and the need for sustainable policy support. This article concludes that developing a curriculum that integrates Islamic educational values and local wisdom is an effective, innovative, and sustainable educational strategy to shape a young generation that is religious, cultured, and competitive in the modern era.